ORGANIZATION OF MEDICAL CARE FOR VICTIMS ON THE HIGHWAY M-4 «DON» - Y. I. Vovk; V. I. Ivanov; V. A. Sarkisjan; S. G. Chesnikov; B. E. Gurkin; D. V. Ivanov; A. S. Kalintsev; N. P. Lopukhin (Медицинский вестник Юга России, 2014)
Purpose: To clarify the number of traffic accidents on the federal highway M-4 «Don» in the Rostov region and to justify the necessity of principal approach to the solution of medical care problems to the victims on the highway.Materials and methods: The analysis of traffic accidents on the federal highway M-4 «Don» from 2007 to 2012 was carried out; the results of the regional law action “Improving of traffic safety on the Rostov region” from 11.01.2007 № 609 and the basic indices of Rostov region medical institutions activity according to the realization of measures aimed at the organization of medical care for victims on the highway were analyzed.Results: the positive dynamics by the main indices of medical care organization, reducing of the death-roll at the pre-hospital stage and during the transport by ambulances and reducing the number of deaths in traumatology centers were noted.Summary: being equipped with modern medical transports, modern medical X-ray equipments, the availability of experienced medical personnel and an efficient interaction of all levels traumatology centers the hospitals can improve the quality of medical care to the victims on the highway.